2005
DOI: 10.1055/s-2004-821255
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Isolated Intestinal Perforation and Necrotizing Enterocolitis

Abstract: Comparing the groups, we found statistical significant differences in isolated perforation cases with these risk factors: extreme prematurity, very low birth weight, abruptio placenta, intubation and neonatal mechanical ventilation, umbilical catheterization, precocious sepsis, and indomethacin therapy. A more precocious operation and a good prognosis also reached statistical significance. In the other hand, we found statistically significant differences in NEC with congenital cardiopathy (excluding isolated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…The latter type of perforation is less well defined and appears in the literature under different names: spontaneous intestinal perforation, idiopathic intestinal perforation, focal intestinal perforation, or focal NEC [1,3,7,9,10]. Besides ischemic pathogenesis [10], the hypoperistalsis of immature bowel (ileus of prematurity) seems to be the main pathogenetic factor of perforation in ELBW neonates [7,11].…”
Section: Discussionmentioning
confidence: 99%
“…The latter type of perforation is less well defined and appears in the literature under different names: spontaneous intestinal perforation, idiopathic intestinal perforation, focal intestinal perforation, or focal NEC [1,3,7,9,10]. Besides ischemic pathogenesis [10], the hypoperistalsis of immature bowel (ileus of prematurity) seems to be the main pathogenetic factor of perforation in ELBW neonates [7,11].…”
Section: Discussionmentioning
confidence: 99%
“…16,38 Discontinuity or defects in the intestinal muscular layer and alteration in intestinal mucosal and muscular morphology by glucocorticoids (dexamethasone) have also been implicated as contributing factors to IIP. [45][46][47][48] The association between early postnatal indomethacin exposure and IIP may also have to do with the timing of exposure. One group of investigators reported negative end-diastolic flow velocity in one infant and absent end-diastolic flow velocity in seven preterm infants on day one of life.…”
Section: Nec Vs Iipmentioning
confidence: 99%
“…[15] Localised or idiopathic perforation accounts for one-third of all CP, but we found it in only 9 (15%) of patients. [15] The probable explanation is that our sample population included only full term neonate and infants, while idiopathic perforation occure mostly in low birth-weight babies.…”
Section: Discussionmentioning
confidence: 49%
“…[13,14] Localised or idiopathic perforation was described by Breslau in 1863 as "the perforation for which no other cause or NEC is found." [15] Usually, it occurs in low or very low birth-weight infants in whom traumatic delivery, congenital defects of the bowel with diverticulum formation, localised vascular insufficiency and intrauterine or post-partum infection have occurred. [15] Localised or idiopathic perforation accounts for one-third of all CP, but we found it in only 9 (15%) of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation